Deteksi Dini Krisis Keuangan di Indonesia: Determinan Makro Ekonomi tahun 1996-2013 - Erbaviantha, Brigita Vegy (Jurnal Ilmiah Mahasiswa FEB, 2016)
The aim of this study is to analyze the determinants that affect the financial crisis in Indonesia. The determinants were Real Exchange Rate,  foreign  reserves growth, net export-import,  lending and deposit ratio, world oil price. This study using descriptive analysis. The  results showed  that Real Exchange Rate, foreign reserves growth, net export-import, lending and deposit ratio, world oil  price  had  a  effect  on  financial  crisis  in  Indonesia.  The  recommendation  of  this  study  is government need  to develop an early warning system with  the appropriate approach  to economy condition of Indonesia in order to avoid the wider financial crisis.Keywords  :  Financial  Crisis,  Real  Exchange  Rate,  foreign  reserves  growth,  net  export-impor, lending and deposit ratio, world oil price.